Transformational leadership in elite sport: A qualitative analysis of effective leadership behaviors in cricket - Smith, M. J.; Young, D. J.; Figgins, S. G.; Arthur, C. A. (The Sport Psychologist, 2017)
We examined transformational leadership behaviors are exhibited in an elite sport environment. Semistructured interviews were conducted with 9 professional county cricket players to explore perceptions of transformational leadership behaviors of their captain and head-coach. Behaviors were firstly deductively categorized based on the Differentiated Transformational Leadership Inventory, with the most frequently cited being high performance expectations and individual consideration from the coach, and appropriate role-modeling of the captain. Further inductive analyses revealed a range of other factors which may influence players` perceptions of transformational leadership. From these findings, suggestions are offered for those working in an applied context with sporting leaders.